2018
DOI: 10.1007/s40520-018-0933-x
|View full text |Cite
|
Sign up to set email alerts
|

Waist circumference is a better predictor of risk for frailty than BMI in the community-dwelling elderly in Beijing

Abstract: Abdominal obesity is more closely associated with incidence of frailty than general obesity in the elderly. Older adults with large waist circumference are more likely to be frail. Frailty in the elderly might be more closely related to metabolic disorders. WC might be a better measurement to detect frailty than BMI, given its relationship with metabolic disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
44
2
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 42 publications
7
44
2
4
Order By: Relevance
“…In the present study, obesity was also associated with a higher risk of frailty before adjusting for WHtR, but it was not associated with the risk of frailty after adjusting for WHtR. Previous epidemiological studies consistently reported that abdominal obesity defined by WC (8,9,16,17,40) and WHtR (21) was associated with a higher prevalence and incidence of frailty in the older adults. Older adults with high WC had high levels of oxidative stress markers, independent of BMI, suggesting a possible involvement of oxidative stress in the genesis of frailty (18,19) .…”
Section: Discussioncontrasting
confidence: 44%
See 1 more Smart Citation
“…In the present study, obesity was also associated with a higher risk of frailty before adjusting for WHtR, but it was not associated with the risk of frailty after adjusting for WHtR. Previous epidemiological studies consistently reported that abdominal obesity defined by WC (8,9,16,17,40) and WHtR (21) was associated with a higher prevalence and incidence of frailty in the older adults. Older adults with high WC had high levels of oxidative stress markers, independent of BMI, suggesting a possible involvement of oxidative stress in the genesis of frailty (18,19) .…”
Section: Discussioncontrasting
confidence: 44%
“…Garcia-Esquinas et al (16) reported that obesity was positively associated with the risk of frailty in the older adults, but the association was not significant after adjusting for waist circumference (WC), suggesting that the association between BMI and frailty could be mediated by abdominal obesity. A few previous studies reported that abdominal obesity was associated with higher prevalence and incidence of frailty in the older adults (8,9,16,17) . Increased WC has been suggested to be associated with a marker of oxidative stress and inflammation, independent of BMI (18) , which may be the major mechanism leading to frailty (19) .…”
mentioning
confidence: 98%
“…The prevalence of frailty increased with low BMI. Our ndings corroborate the views that a lower BMI may indicate insu cient reserve capacity and weight loss, which was a key factor in the formation of frailty [44]. Underweight may be due to chronic illness or malnutrition and sarcopenia, which were also associated with increased risk of frailty [45].…”
Section: Discussionsupporting
confidence: 87%
“…Previous analyses within Nutrition UP 65 had shown that overweight and obesity assessed by BMI were associated with slow GS . However, the BMI can be more prone to errors in the estimation of the body composition of older adults . First, older individuals are generally shorter than younger adults .…”
Section: Discussionmentioning
confidence: 99%
“…16 However, the BMI can be more prone to errors in the estimation of the body composition of older adults. [41][42][43] First, older individuals are generally shorter than younger adults. 42 Second, the amount of muscle mass decreases with age in sarcopenia, and the BMI does not distinguish fat mass from fat-free mass.…”
Section: Discussionmentioning
confidence: 99%